COMPREHENSIVE EPIDEMIOLOGICAL ANALYSIS OF THE TUBERCULOSIS SITUATION AMONG THE DIFFERENT ETHNIC GROUPS OF THE BURYATIA - V. A. Astafyev; E. D. Savilov; L. A. Stepanenko; A. N. Zarbuev; O. B. Ogarkov; S. N. Zhdanova; L. S. Untanova (Acta Biomedica Scientifica, 2013)
Comprehensive epidemiological analysis of tuberculosis in the Republic of Buryatia (RB), including among different ethnicgroups (Russian, Buryat, Evenk) presents in the article. Assessment of the epidemiological situationfor 1994-2012 was examined on various parameters (incidence, prevalence and mortality). It was found that the epidemiological situation in RB in the last twenty years were characterized by high incidence of tuberculosis when compared with similar data for Russia as a whole (mean annual incidence 148,1 ± 6,90/0000 и 77.6 ± 2,10/0000 respectively). Among the various ethnic groups living in the RB, the most unfavorable epidemiological indicators identified for the Buryat population. "Safely" group of the population was Evenki. For each of the studied ethnic groups have been identified areas of tuberculosis risk, which had its own characteristics.